Faktor-Faktor yang Berhubungan dengan Perilaku SADARI pada Remaja Putri di SMAN 1 Tekarang - Umi Fania Julianti (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Breast cancer is a type of disease affecting the supporting tissue in the breast. In Indonesia, breast cancer is the leading cause of cancer death among women. Early detection of breast cancer is very important to be done as soon as possible through SADARI behavior because if an abnormality in the breast is detected early, clinical examination can be conducted promptly. Research objective: to identify the factors associated with SADARI behavior among female adolescents at SMAN 1 Tekarang. Research method: This study is quantitative with an analytical approach using a cross-sectional time approach. The study was conducted at SMAN 1 Tekarang from April 5, 2025, to May 21, 2025. The study population consisted of 217 female students at SMAN 1 Tekarang, while the sampling technique used was accidental sampling, resulting in 187 samples. The variables studied were the dependent variable of SADARI behavior and independent variables of attitude, health literacy, information exposure, and family health history with breast cancer. Data collection using a questionnaire. Analysis using the Chi Square test. The results of the analysis showed no relationship between attitudes (ρ value 0.073) and health lateracy (ρ value 0.959) with SADARI behavior, while there was a relationship between information exposure (ρ value 0.000) and family health history of breast cancer (ρ value 0.000) with SADARI behavior. Conclusion: There is a statistical relationship between information exposure and family health history with BSE behavior.